A rare bilateral variation on the dorsum of the hand: extensor digitorum brevis manus and extensor medii proprius - Lee, Dong Hyun (Anat Cell Biol, 2019)
A 78-year-old male cadaver showed bilateral anomalous muscles on the dorsum of the hand. An extensor digitorum brevis manus was noted on the dorsum of the right hand. It originated from the distal end of the radius and the radiocarpal joint ligaments and inserted into the metacarpophalangeal joint of the third digit. On the dorsum of the left hand, an extensor digiti medii proprius was identified. It originated from the distal third of the ulna near the extensor indicis proprius and the interosseous membrane and inserted into the metacarpophalangeal joint of the third digit. Awareness of these combined muscular variation would be helpful in understanding the identification of digital extensors and in requiring careful consideration for the reconstruction surgery of the hand.